(untitled) (Research, Society and Development, 2023)
Mozambique is an agricultural country. However, it faces numerous challenges to feed the population and reduce poverty. Recently, the situation is being worsened by high environmental, social vulnerability and extreme events influenced by climate disruption in the form of cyclones, droughts, and floods. Sustainable use of resources has become an issue in each food supply chain segment. People often suffer from food shortages: some caused by natural disasters, others by excessive post-harvest losses due poor storage facilities. Therefore, reducing post-harvest losses through preservation technologies is an important step toward reaching ending hunger (SDG 2) and ensuring sustainable consumption and production patterns (SDG 12). Thus, practical ways of cheaply and sanitarily preserving foods are needed. The post-harvest losses of agricultural products can be reduced drastically by using renewable energy sources like solar energy. This article presents a review and possibilities of using solar drying, focusing on the technical needs of small farmers in Mozambique. In this study, it was concluded that solar drying is one of the most efficient and cost-effective, renewable, and sustainable technologies to conserve agricultural products. However, solar dryers, being used in Mozambique, are only useful in the presence of solar radiation and useless at night or during cloudy days. To enable off-sun drying, heat storage must be integrated. This way, it can trigger the hopes for alleviation of poverty, opportunity for decent work, economic growth and reduce inequality.